Comparison of Kidney Extraction Incisions in Laproscopic Living Donor Nephrectomy: A Single-Center Experience. (July 2018) - Ayvazoglu Soy, Ebru H.; Karakayali, Feza Yarbug; Ozcelik, Umit; Moray, Gokhan; Torgay, Adnan; Haberal, Mehmet
Abstract : Introduction: Laparoscopic donor nephrectomy has become alternative to the open procedure. Many studies comparing techniques and extraction incisions during laparoscopic donor nephrectomy have been reported. Here our aim is to compare our Pfannenstiel and extended iliac port site incisions for kidney extraction in transperitoneal laparoscopic donor nephrectomy. Materials and Methods: Between October 1985 and October 2017 we performed 2781 kidney transplantation procedures at our centers. Since January 2015, we performed 54 laparoscopic transperitoneal donor nephrectomies. Kidney retrieval were done through either Pfannenstiel incision or extended iliac port incision. Two groups were compared according to demographic features, graft weight, warm ischemia, hospital stay and cosmetic results. Results: In group 1; 21 kidneys were extracted through Pfannenstiel incision. In group 2; 34 kidneys were retrieved via extended iliac port incisions. There were not any statistical difference between group 1 and 2 with respect to BMI (mean 24.73 vs 25.29), graft weight (mean 184.66 gr vs 206.06 gr) and hospital stay (mean 1.5 vs 1.8 days). However, warm ischemia time was significantly shorter in group 2 (mean 248.09 vs 166.21 seconds) (p< .001). The cosmetic results were analyzed with POSAS scale and in Pfannenstiel incision group cosmetic results were much more better. Conclusion: In living donor nephrectomy kidney retrieval procedure should be safe and comfortable, without compromising the function of the graft. To date several modifications of the standard transperitoneal laparoscopic approach have been applied and each of them claim to have specific advantages. According to our experience, extraction of kidney through extended iliac port incision has worse cosmetic results but significantly short warm ischemia time than Pfannenstiel incision.